2020
DOI: 10.1002/brb3.1622
|View full text |Cite
|
Sign up to set email alerts
|

Network changes in patients with phobic postural vertigo

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 51 publications
1
8
0
1
Order By: Relevance
“…Connectivity studies also demonstrated reduced resting-state functional connectivity between visual, vestibular, and spatial cognition areas ( Lee et al, 2018 ; Li et al, 2020 ). Importantly, a special role of the cerebellum is highlighted ( Lee et al, 2018 ; Huber et al, 2020 ): during a visual motion task, for example, cerebellar network activity of functional dizziness patients was reduced, whereas during static visual scenes, it was increased ( Huber et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Connectivity studies also demonstrated reduced resting-state functional connectivity between visual, vestibular, and spatial cognition areas ( Lee et al, 2018 ; Li et al, 2020 ). Importantly, a special role of the cerebellum is highlighted ( Lee et al, 2018 ; Huber et al, 2020 ): during a visual motion task, for example, cerebellar network activity of functional dizziness patients was reduced, whereas during static visual scenes, it was increased ( Huber et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…As physical examination, clinical laboratory testing and vestibular evaluation may be normal in PPPD [21,22], advances in neuroimaging have provided new insights in patients with PPPD illustrating the delicate changes in functional activity and internetwork connectivity involving the vestibular, visual and emotion processing centers [10,12,13,24,26]. However, the functional MRI is not easily available and diagnosis relies heavily on clinical history [21].…”
Section: Introductionmentioning
confidence: 99%
“…The increased in activation was seen when static visual stimulus was given. However, cerebellar activation was reduced when a visual motion stimuli was used and this was accompanied by increase in the sensorimotor network (23). Patients with PPPD also did not show the increased activation motion in the third short insular gyrus and adjacent Rolandic operculum which was seen in the healthy controls during vertical to horizontal (23).…”
Section: Resultsmentioning
confidence: 78%